Investigating the chemical constituent and the suppressive effects of alliin hydrolysate on E.coli - Tao Wu; Ning Chen; Chang Liu; Rui Liu; Jiaojiao Zhang; Xuan Xie; Min Zhang (Natural Product Research, 2017)

Photoperiodism dynamics during the domestication and improvement of soybean - Sheng-Rui Zhang; Huan Wang; Zhongyu Wang; Yao Ren; Lifang Niu; Jun Liu; Bin Liu (Science China Life Sciences, 2017)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Mechanisms of Acupuncture Therapy for Cerebral Ischemia: an Evidence-Based Review of Clinical and Animal Studies on Cerebral Ischemia - Wen Zhu; Yang Ye; Yi Liu; Xue-Rui Wang; Guang-Xia Shi; Shuai Zhang; Cun-Zhi Liu (Journal of Neuroimmune Pharmacology, 2017)

The use of toluidine blue staining combined with paraffin sectioning and the optimization of freeze-thaw counting methods for analysing root-knot nematodes in tomato - Xiaoman Li; Wenchao Zhao; Xiaoxuan Zhou; Jiaping Feng; Yingjian Gao; Xuehui Yao; Yang Liu; Jie Liu; Rui Yang; Fukuan Zhao; Shaohui Wang (Horticulture, Environment, and Biotechnology, 2017)

Pollution characteristics and ecological risk assessment of HCHs and DDTs in estuary wetland sediments from the Bohai Bay, North China - Qing Liu; Shengyan Tian; Rui Jia; Xianbin Liu (Environmental Science and Pollution Research, 2017)

The N-terminal and central domain of colicin A enables phage lysin to lyse Escherichia coli extracellularly - Guangmou Yan; Jianfang Liu; Qiang Ma; Rining Zhu; Zhimin Guo; Chencheng Gao; Shuang Wang; Ling Yu; Jingmin Gu; Dongliang Hu; Wenyu Han; Rui Du; et al. (Antonie van Leeuwenhoek, 2017)

Phenylpropanoids from the fruits of Nicandra physaloides and their anti-inflammatory activities - Bing You Yang; Yan Liu; Hai Bing Jiang; Zhen Peng Xu; Rui Guo; Rui Wang; Xiao Mao Li; Hai Xue Kuang (Natural Product Research, 2017)

Fine-mapping and identification of a novel locus Rsc15 underlying soybean resistance to Soybean mosaic virus - Ren Rui; Shichao Liu; Adhimoolam Karthikeyan; Tao Wang; Haopeng Niu; Jinlong Yin; Yunhua Yang; Liqun Wang; Qinghua Yang; Haijian Zhi; Kai Li (Theoretical and Applied Genetics, 2017)

New Botanical Anxiolytics for Use in Companion Animals and Humans - Rui Liu; Fida Ahmed; Christian Cayer; Martha Mullally; Ana Francis Carballo; Marco Otarola Rojas; Mario Garcia; John Baker; Aleksandar Masic; Pablo E Sanchez; Luis Poveda; Zul Merali; et al. (The AAPS Journal, 2017)

Profiling methyl jasmonate-responsive transcriptome for understanding induced systemic resistance in whitebark pine (Pinus albicaulis) - Jun-Jun Liu; Holly Williams; Xiao Rui Li; Anna W. Schoettle; Richard A. Sniezko; Michael Murray; Arezoo Zamany; Gary Roke; Hao Chen (Plant Molecular Biology, 2017)

A new biphenyl derivative from the mangrove endophytic fungus Phomopsis longicolla HL-2232 - Xiao-Bao Li; Guang-Ying Chen; Rui-Jie Liu; Cai-Juan Zheng; Xin-Ming Song; Chang-Ri Han (Natural Product Research, 2017)

Association of ACYP2 and TSPYL6 Genetic Polymorphisms with Risk of Ischemic Stroke in Han Chinese Population - Yiqian Liang; Rui Zhang; Shuo Zhang; Guofa Ji; Puyu Shi; Tian Yang; Feng Liu; Jing Feng; Chunqi Li; Dangshe Guo; Mingwei Chen (Molecular Neurobiology, 2017)

Protective effect of Ganoderma lucidum polysaccharide against carbon tetrachloride-induced hepatic damage in precision-cut carp liver slices - Yingjuan Liu; Chunyun Zhang; Jinliang Du; Rui Jia; Liping Cao; Galina Jeney; Hiroki Teraoka; Pao Xu; Guojun Yin (Fish Physiology and Biochemistry, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Improved GNSS-based indoor positioning algorithm for mobile devices - Rui Xu; Wu Chen; Ying Xu; Shengyue Ji; Jianye Liu (GPS Solutions, 2017)

Assessment of PPP integer ambiguity resolution using GPS, GLONASS and BeiDou (IGSO, MEO) constellations - Yanyan Liu; Yidong Lou; Shirong Ye; Rui Zhang; Weiwei Song; Xing Zhang; Qingquan Li (GPS Solutions, 2017)

Stocking density effects on growth and stress response of juvenile turbot (Scophthalmus maximus) reared in land-based recirculating aquaculture system - Baoliang Liu; Rui Jia; Kuifeng Zhao; Guowen Wang; Jilin Lei; Bin Huang (Acta Oceanologica Sinica, 2017)

The ArfGAP protein MoGlo3 regulates the development and pathogenicity of Magnaporthe oryzae - Shengpei Zhang; Xiu Liu; Lianwei Li; Rui Yu; Jialiang He; Haifeng Zhang; Xiaobo Zheng; Ping Wang; Zhengguang Zhang (Environmental Microbiology, 2017)
Summary The ADP ribosylation factor (Arf) and the coat protein complex I (COPI) are involved in vesicle transport. Together with GTPase‐activating proteins (ArfGAPs) and guanine exchange factors (ArfGEFs) that regulate the activity of Arf, they govern vesicle formation, COPI trafficking and the maintenance of the Golgi complex. In an ongoing effort to study the role of membrane trafficking in pathogenesis of the rice blast fungus Magnaporthe oryzae , we identified MoGlo3 as an ArfGAP protein that is homologous to Glo3p of the budding yeast Saccharomyces cerevisiae . As suspected, MoGlo3 partially complements the function of yeast Glo3p. Consistent with findings in S. cerevisiae , MoGlo3 is localized to the Golgi, and that the localization is dependent on the conserved BoCCS domain. We found that MoGlo3 is highly expressed during conidiation and early infection stages and is required for vegetative growth, conidial production and sexual development. We further found that the Δ Moglo3 mutant is defective in endocytosis, scavenging of the reactive oxygen species, and in the response to endoplasmic reticulum (ER) stress. The combined effects result in failed appressorium function and decreased pathogenicity. Moreover, we provided evidence showing that the domains including the GAP, BoCCS and GRM are all important for normal MoGlo3 functions. Our studies further illustrate the importance of normal membrane trafficking in the physiology and pathogenicity of the rice blast fungus.

Robustness-Optimality Tradeoff for Watershed Load Reduction Decision Making under Deep Uncertainty - Han Su; Feifei Dong; Yong Liu; Rui Zou; Huaicheng Guo (Water Resources Management, 2017)

Genetic and transcriptomic analyses of lignin- and lodging-related traits in Brassica napus - Lijuan Wei; Hongju Jian; Kun Lu; Nengwen Yin; Jia Wang; Xiujian Duan; Wei Li; Liezhao Liu; Xinfu Xu; Rui Wang; Andrew H. Paterson; Jiana Li (Theoretical and Applied Genetics, 2017)

An anther-specific gene PhGRP is regulated by PhMYC2 and causes male sterility when overexpressed in petunia anthers - Yuanzheng Yue; Chaoqun Yin; Rui Guo; Hao Peng; Zhaonan Yang; Guofeng Liu; Manzhu Bao; Huirong Hu (Plant Cell Reports, 2017)

Effects of Cd on reductive transformation of lepidocrocite by Shewanella oneidensis MR-1 - Chaolei Yuan; Fangbai Li; Rui Han; Tongxu Liu; Weimin Sun; Weilin Huang (Acta Geochimica, 2017)

Phenotypic Variation and Genetic Diversity in the Collections of Erianthus Arundinaceus (Retz.) Jesw. - Xi-Hui Liu; Huan-Zhong Song; Ge-Min Zhang; Wei-Xing Duan; Rong-Hua Zhang; Yang-Rui Li (Sugar Tech, 2017)

Genome re-sequencing analysis uncovers pathogenecity-related genes undergoing positive selection in Magnaporthe oryzae - Jidong Cao; Yongqi Yu; Junkai Huang; Rui Liu; Yan Chen; Suiyan Li; Jun Liu (Science China Life Sciences, 2017)

Research on differences of spillover effects between international crude oil price and stock markets in China and America - Zhenhua Liu; Zhihua Ding; Rui Li; Xin Jiang; JyS. Wu; Tao Lv (Natural Hazards, 2017)

Enhanced dissipation of DEHP in soil and simultaneously reduced bioaccumulation of DEHP in vegetable using bioaugmentation with exogenous bacteria - Hai-Ming Zhao; Rui-Wen Hu; He-Biao Huang; Hong-Fei Wen; Huan Du; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo; Jie-Sheng Liu; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Inhibitory effect of StCYP707A1 gene on tuberization in transgenic potato - Lu Liu; Rui-Jie Zhang; Wen-Jiao Zhu; Xin-Ru Liu; Ke Shi; Min Chen; Qing Yang (Plant Biotechnology Reports, 2017)

Molecular Mechanisms of Vascular Dementia: What Can Be Learned from Animal Models of Chronic Cerebral Hypoperfusion? - Si-Qi Du; Xue-Rui Wang; Ling-Yong Xiao; Jian-Feng Tu; Wen Zhu; Tian He; Cun-Zhi Liu (Molecular Neurobiology, 2017)

Puerarin may protect against Schwann cell damage induced by glucose fluctuation - Bing Xue; Lin Wang; Zhe Zhang; Rui Wang; Xin-xin Xia; Ping-ping Han; Li-jun Cao; Yong-hui Liu; Lian-qing Sun (Journal of Natural Medicines, 2017)

The effect of Mg2+ on digestion performance and microbial community structures in sludge digestion systems - CongCong Liu; Cheng Huang; XiuYun Sun; Rui Li; Jiansheng Li; Jinyou Shen; Weiqing Han; Lianjun Wang (Environmental Science and Pollution Research, 2017)

Holocene activity evidence on the southeast boundary fault of Heqing basin, middle segment of Heqing-Eryuan fault zone, West Yunnan Province, China - Chang-bin Sun; De-wen Li; Xiao-ming Shen; Yan-rui Kang; Rui Liu; Ya-jiao Zhang (Journal of Mountain Science, 2017)

Three new phenylpropanoids from Lavandula angustifolia and their bioactivities - Shiyun Tang; Jianlian Shi; Chunbo Liu; Rui Jiang; Wei Zhao; Xin Liu; Nengjun Xiang; Yongkuan Chen; Qinpeng Shen; Mingming Miao; Zhihua Liu; Guangyu Yang (Natural Product Research, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

ATP-Citrate Lyase Gene (SoACLA-1), a Novel ACLA Gene in Sugarcane, and Its Overexpression Enhance Drought Tolerance of Transgenic Tobacco - Thi-Thu Phan; Jian Li; Bo Sun; Jia-Yi Liu; Wen-Hui Zhao; Chan Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Plasminogen activator inhibitor links obesity and thrombotic cerebrovascular diseases: The roles of PAI-1 and obesity on stroke - Rui Chen; Jinchuan Yan; Peijing Liu; Zhongqun Wang; Cuiping Wang (Metabolic Brain Disease, 2017)

Characterization and speciation of mercury in mosses and lichens from the high-altitude Tibetan Plateau - Jun-juan Shao; Cheng-bin Liu; Qing-hua Zhang; Jian-jie Fu; Rui-qiang Yang; Jian-bo Shi; Yong Cai; Gui-bin Jiang (Environmental Geochemistry and Health, 2017)

Characterization of angiotensin-І converting enzyme inhibiting peptide from Venerupis philippinarum with nano-liquid chromatography in combination with orbitrap mass spectrum detection and molecular docking - Lei Shi; Tizhi Wu; Naijuan Sheng; Li Yang; Qian Wang; Rui Liu; Hao Wu (Journal of Ocean University of China, 2017)

Isorhamnetin protects against cardiac hypertrophy through blocking PI3K–AKT pathway - Lu Gao; Rui Yao; Yuzhou Liu; Zheng Wang; Zhen Huang; Binbin Du; Dianhong Zhang; Leiming Wu; Lili Xiao; Yanzhou Zhang (Molecular and Cellular Biochemistry, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Phytotoxicity of CeO2 nanoparticles on radish plant (Raphanus sativus) - Xin Gui; Mengmeng Rui; Youhong Song; Yuhui Ma; Yukui Rui; Peng Zhang; Xiao He; Yuanyuan Li; Zhiyong Zhang; Liming Liu (Environmental Science and Pollution Research, 2017)

Functional characterization of a pathogenesis-related protein family 10 gene, LrPR10-5, from Lilium regale Wilson - Rui Chen; Hua He; Ye Yang; Yuan Qu; Feng Ge; Diqiu Liu (Australasian Plant Pathology, 2017)

A novel genetic algorithm for optimization of conditioning factors in shallow translational landslides and susceptibility mapping - Long Li; Rui Liu; Saied Pirasteh; Xianhua Chen; Long He; Jonathan Li (Arabian Journal of Geosciences, 2017)

Folate-Functionalized Lipid Nanoemulsion to Deliver Chemo-Radiotherapeutics Together for the Effective Treatment of Nasopharyngeal Carcinoma - Ying Liu; Xue-Min Yu; Rui-Jie Sun; Xin-Liang Pan (AAPS PharmSciTech, 2017)

Effects of Cold Stress on Root Growth and Physiological Metabolisms in Seedlings of Different Sugarcane Varieties - Bo Sun; Guang-Ling Liu; Thi Thu Phan; Li-Tao Yang; Yang-Rui Li; Yong-Xiu Xing (Sugar Tech, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Land use legacies and nitrogen fertilization affect methane emissions in the early years of rice field development - Rui Shao; Ming Xu; Renqiang Li; Xiaoqin Dai; Lixiang Liu; Ye Yuan; Huimin Wang; Fengting Yang (Nutrient Cycling in Agroecosystems, 2017)

Effects of DDIT4 in Methamphetamine-Induced Autophagy and Apoptosis in Dopaminergic Neurons - Bing Li; Rui Chen; Ling Chen; Pingming Qiu; Xiuyun Ai; Enping Huang; Weiye Huang; Chuanxiang Chen; Chao Liu; Zhoumeng Lin; Wei-Bing Xie; Huijun Wang (Molecular Neurobiology, 2017)

Oxygen microprofiles within the sediment-water interface studied by optode and its implication for aeration of polluted urban rivers - Bo Liu; Rui-ming Han; Wen-lin Wang; Hong Yao; Feng Zhou (Environmental Science and Pollution Research, 2017)

Does residual H2O2 result in inhibitory effect on enhanced anaerobic digestion of sludge pretreated by microwave-H2O2 pretreatment process? - Jibao Liu; Ruilai Jia; Yawei Wang; Yuansong Wei; Junya Zhang; Rui Wang; Xing Cai (Environmental Science and Pollution Research, 2017)

Oxygen isotope clue to migration of dolomitizing fluid as exampled by the Changxing Formation dolomite at Panlongdong, northeastern Sichuan - Rui Zhao; Yasheng Wu; Hongxia Jiang; Qingsong Liu (Journal of Earth Science, 2017)

Performance analysis of a Kalman filter carrier phase tracking loop - Rui Jiang; Kedong Wang; Shihan Liu; Yong Li (GPS Solutions, 2017)

GLONASS phase bias estimation and its PPP ambiguity resolution using homogeneous receivers - Yanyan Liu; Weiwei Song; Yidong Lou; Shirong Ye; Rui Zhang (GPS Solutions, 2017)

Elevated Serum Brain-Derived Neurotrophic Factor (BDNF) but not BDNF Gene Val66Met Polymorphism Is Associated with Autism Spectrum Disorders - Wei-Dong Meng; Shao-Jun Sun; Jie Yang; Rui-Xue Chu; Wenjun Tu; Qiang Liu (Molecular Neurobiology, 2017)

IP-10/CXCR3 Axis Promotes the Proliferation of Vascular Smooth Muscle Cells through ERK1/2/CREB Signaling Pathway - Hui-jin Wang; Yu Zhou; Rui-ming Liu; Yuan-sen Qin; Ying-huan Cen; Ling-yu Hu; Shen-ming Wang; Zuo-jun Hu (Cell Biochemistry and Biophysics, 2017)

Evolution of a large intracranial artery dissection on multimodal neuroimaging with spontaneous healing - Qiao Zuo; Yi-bin Fang; Rui Zhao; Jian-min Liu; Qing-hai Huang (Acta Neurologica Belgica, 2017)

Isolation, chemical characterization, and immunomodulatory activity of naturally acetylated hemicelluloses from bamboo shavings - Ju-qing Huang; Rui-ting Qi; Mei-rong Pang; Cong Liu; Guang-yu Li; Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

Validation of the quantitative trait locus underlying soybean plant height using residual heterozygous lines and near-isogenic lines across multi-environments - Long Yan; Yuanyuan Zhang; Qijian Song; Perry B. Cregan; Chunyan Yang; Yongqiang Charles An; Chengjun Wu; Qiang Chen; Bingqiang Liu; Rui Di; Mengchen Zhang (Euphytica, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Seroprevalence investigation of bovine ephemeral fever in yaks in Tibetan Plateau of China from 2012 to 2015 - Dongyu Liu; Kun Li; Lihong Zhang; Yanfang Lan; Xiaoqiang Wang; Hui Zhang; Lei Wang; Rui Gui; Zhaoqing Han; Wenteng Jang; Suolang Sizhu; Jiakui Li (Tropical Animal Health and Production, 2017)

Efficient Generation of Functionally Active Spinal Cord Neurons from Spermatogonial Stem Cells - Hao Yang; Cuicui Liu; Bo Chen; Jing An; Rui Zhang; Qian Zhang; Jingjing Zhao; Baorong He; Ding-Jun Hao (Molecular Neurobiology, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

Erratum to: Glycogen synthase kinase 3 (GSK3)-inhibitor SB216763 promotes the conversion of human umbilical cord mesenchymal stem cells into neural precursors in adherent culture - Liyang Gao; Mingyan Zhao; Peng Li; Junchao Kong; Zhijun Liu; Yonghua Chen; Rui Huang; Jiaqi Chu; Juanhua Quan; Rong Zeng (Human Cell, 2017)

Glycogen synthase kinase 3 (GSK3)-inhibitor SB216763 promotes the conversion of human umbilical cord mesenchymal stem cells into neural precursors in adherent culture - Liyang Gao; Mingyan Zhao; Peng Li; Junchao Kong; Zhijun Liu; Yonghua Chen; Rui Huang; Jiaqi Chu; Juanhua Quan; Rong Zeng (Human Cell, 2017)

Evaluation of pulsed corona discharge plasma for the treatment of petroleum-contaminated soil - Rui Li; Yanan Liu; Ruiwen Mu; Wenyan Cheng; Stéphanie Ognier (Environmental Science and Pollution Research, 2017)

The effect of temperature and moisture on the source of N2O and contributions from ammonia oxidizers in an agricultural soil - Rui Liu; Helen L. Hayden; Helen Suter; Hangwei Hu; Shu Kee Lam; Jizheng He; Pauline M. Mele; Deli Chen (Biology and Fertility of Soils, 2017)